2015
DOI: 10.1371/journal.pone.0131817
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotype of the C9ORF72 Expansion Carriers According to Revised Criteria for bvFTD

Abstract: BackgroundThe C9ORF72 expansion is one of the most common genetic etiologies observed with behavioural variant frontotemporal dementia (bvFTD). Revised diagnostic criteria for bvFTD (FTDC) were recently introduced but only a few studies have evaluated the accuracy of these criteria.ObjectiveThe objective of the study was to evaluate the applicability of the FTDC criteria and assess the psychiatric history of these patients.MethodsThe study examined 36 patients carrying the C9ORF72 expansion and suffering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 18 publications
1
39
1
1
Order By: Relevance
“…Although recent studies have increasingly reported elevated NfL levels in several neurodegenerative conditions, such as FTLD, AD and PD, the role of NfL in primary psychiatric disorders has remained unclear [4]. The fact that the phenotypes under the FTLD spectrum show a significant clinical overlap with psychiatric disorders [1][2][3], but substantially differ in the underlying pathophysiology, highlights the importance of minimally invasive pathophysiological biomarkers differentiating these two etiologies. In this present study, we have shown that sNfL levels are higher in FTLD spectrum disorder patients compared to those with PPD, which is in line with a previous report on CSF samples [12] and a recent study with serum samples [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have increasingly reported elevated NfL levels in several neurodegenerative conditions, such as FTLD, AD and PD, the role of NfL in primary psychiatric disorders has remained unclear [4]. The fact that the phenotypes under the FTLD spectrum show a significant clinical overlap with psychiatric disorders [1][2][3], but substantially differ in the underlying pathophysiology, highlights the importance of minimally invasive pathophysiological biomarkers differentiating these two etiologies. In this present study, we have shown that sNfL levels are higher in FTLD spectrum disorder patients compared to those with PPD, which is in line with a previous report on CSF samples [12] and a recent study with serum samples [6].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of frontotemporal lobar degeneration (FTLD) and especially the behavioral variant frontotemporal dementia (bvFTD) subtype is often challenging, as the heterogeneous clinical manifestation may overlap not only with other neurodegenerative diseases but also with primary psychiatric disorders (PPD) [1][2][3]. Thus, biomarkers with a potential to accurately discriminate diseases with wide-ranging neuropsychiatric phenotypes are needed for early and correct diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These high specificities compared to our findings are probably the result of the selected dementia cohort in this study which included very few patients with psychiatric and vascular diseases that can mimic bvFTD [30]. Two studies of a cohort of patients carrying the C9orf72 hexanucleotide repeat expansion found significantly lower sensitivities of the FTDC criteria for possible bvFTD (75 and 60%) and probable bvFTD (64 and 38%) [19,20]. The lower sensitivities in these studies are probably due to the specific phenotype of the C9orf72 hexanucleotide repeat expansion with early behavioural and psychiatric symptoms, indicating the dilemma of differentiating between bvFTD and psychiatric disorder when using the FTDC criteria.…”
Section: Discussionmentioning
confidence: 55%
“…If deemed appropriate, genetic screening included the MAPT (n = 9), GRN (n = 7), PSEN1 (n = 2) and APP (n = 0) genes. In all subjects in whom DNA was available (n = 137), C9orf72 hexanucleotide repeat expansion was screened for, given the great symptomatic overlap with psychiatric disorders and long disease courses that have been described in this mutation type [16,17,18,19,20]. The study was approved by the Medical Ethical Committee of the VU Medical Centre, Amsterdam.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of both neurological and psychiatric symptoms often observed in FTLD patients led us to hypothesize that FTLD could show comorbidity also with BP. Especially FTLD patients carrying the C9orf72 repeat expansion have psychiatric symptoms prior the neurological diagnosis [28]. Interestingly, the only case with a clinical BP diagnosis in our FTLD cohort was a carrier of the C9orf72 repeat expansion.…”
Section: Discussionmentioning
confidence: 73%